(untitled) (Castilla. Estudios de Literatura, 2017)
By its autrebiographical nature –or autobiography of the other- and its genuine premise –author is dead-, Summertime presents an ontological contradiction that can cause as a result a significant unease in his readers, unable to distinguish between empirical truth and the Truth in Coetzee’s works. In this paper we analyze narrative mechanisms used by the author to prompt readers’ uncertainty and that are related to several cognitive concepts as theory of mind, empathy or differences in processing a fictional or factual work.